1978
DOI: 10.1584/jpestics.3.397
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of Chlorothalonil in Benzene

Abstract: Chlorothalonil (tetrachloroisophtalonitrile) in benzene was unstable at a light place and unknown compounds appeared. This reaction occurred easily by sunlight through glass. A major photolysate of chlorothalonil in benzene was crystallized as colorless needles. The photolysate was identified as 2, 3, 5-trichloro-4, 6-dicyanobiphenyl by means of MS and CMR spectra. Similar photolysates of chlorothalonil occurred easily in other aromatic solvents at the light place and gave 3 peaks in toluene, 1 in o-xylene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Similar values were reported for polychlorobenzenes in cyclohexane. 31 Moreover, we demonstrated that there is also an efficient energy transfer on oxygen with a singlet-oxygen quantum yield close to unity. Thus, most of CT triplet excited state is deactivated in aerated solution, explaining the low CT quantum yield of photodegradation (Φ deg = (2 ( 0.2) Â 10 À2 ).…”
Section: ' Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar values were reported for polychlorobenzenes in cyclohexane. 31 Moreover, we demonstrated that there is also an efficient energy transfer on oxygen with a singlet-oxygen quantum yield close to unity. Thus, most of CT triplet excited state is deactivated in aerated solution, explaining the low CT quantum yield of photodegradation (Φ deg = (2 ( 0.2) Â 10 À2 ).…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…The photolysis of aryl chlorides has been widely studied because of their environmental significance, 32,33 and several paths for the reductive photodechlorination have been proposed. 30,31,34,35 The homolytic cleavage of the CÀCl bond may occur (path a, scheme 1). Alternatively, the reaction may be initiated by an electron transfer by a H-donor molecule followed by a proton transfer to form two radicals (path b, scheme 1).…”
Section: ' Results and Discussionmentioning
confidence: 99%
“…Such an auto-accelerating effect was never mentioned in the literature except by Kawamura et al who irradiated CT in benzene. 7 The decay prole obtained by irradiating CT (2 Â 10 À5 M, acetonitrile-water, 20/80) in deoxygenated solution is shown in Fig. 1B.…”
Section: Steady-state Irradiationmentioning
confidence: 99%
“…[4][5][6] Photolysis in organic solvents or in a solid form is also very slow. 7,8 Interestingly, an auto-accelerated photodegradation was reported in benzene. 7 Concerning photoproducts, different types of reactions are reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation